Phenotypes, Lung Microbiota and Cytokine Responses in Pneumonia After Hematopoietic Stem Cell Transplantation - Hu Y; Jiang Y; Liu S; Shen J; An Y (Journal of Inflammation Research, 2021)
Yan Hu,1 Yanwen Jiang,1 Shuang Liu,1 Jiawei Shen,2 Youzhong An2 1Department of Respiratory and Critical Care Medicine, Peking University International Hospital, Beijing, People’s Republic of China; 2Department of Critical Care Medicine, Peking University People’s Hospital, Beijing, People’s Republic of ChinaCorrespondence: Jiawei Shen; Youzhong AnDepartment of Critical Care Medicine, Peking University People’s Hospital, Beijing, People’s Republic of ChinaEmail jiaweishn@gmail.com; bjicu_bmc@163.comObjective: We aim to identify phenotypes of hematopoietic stem cell transplantation (HSCT) patients with pneumonia, discover relations of microbiota composition, cytokine profile, and outcomes between phenotypes. Specific cytokines will be evaluated for their role in lung injury in a murine model.Methods: HSCT patients with pneumonia were included, and clustering of variables including cytokine levels provided the phenotypes. Outcomes were compared between phenotypes. Analysis of lung microbiota identified marker species of phenotypes. In the murine model, marker species-related cytokine regulations and the role of cytokines in lung injury were evaluated.Results: Seventy-two patients were included, and two phenotypes were identified, namely “reactive” (N=21) and “nonreactive” (N=51) phenotype. Compared to their counterparts, patients with nonreactive phenotype had lower serum IL-6, IL-8, less severe inflammation, worse outcomes and more viruses as marker species in lung microbiota. The animal study validated the pathogens specific cytokine responses that presented in the human study and the potential protective role of IL-6 in these patients.Conclusion: HSCT patients with pneumonia can be clustered into two phenotypes with different marker species and outcomes: the “nonreactive” phenotype and the “reactive” phenotype. Serum cytokine levels were different between the two phenotypes, which indicate the existence of the pathogen-related cytokine responses. For patients with the “nonreactive” phenotype, IL-6 therapy may improve their prognosis, which should be further tested in clinical studies.Keywords: hematopoietic stem cell transplantation, pneumonia, phenotype, microbiota, cytokines